A órbita de uma cena fotografada: o desmentido entre a imagem e o histórico - Gomes, Priscilla Hadassa Rabelo (2023)
This work intended to investigate the imagetic and historical aspects implied in the concept of denial (Verleugnung) from its paradigmatic presentation, the fetishism and some approaches to discussions about photography and history in Walter Benjamin, in order to glimpse its reach. In this way, through the Freudian path, we present the construction of the denial concept, its distinction and its work of formalization, while, through the Benjaminian path, we accentuate the investigated aspects. Therefore, we refer to the notions of image and history, as well as their relations with denial, in the work of Freud, Lacan, in the 1950s seminars, and in Benjamin, mainly in the essay on technical reproducibility. Thus, with a view to the alluded historical character, we present and relate a reading of the notion of origin (Ursprung) in Freud and Benjamin, according to the ideas of leap (Sprung), spring (Springen) and afterwardsness (Nachträglich); then, we show the specificity of Verleugnung in the creation of the fetish object and its metapsychological value, so we can highlight the noncorrespondence between object and goal, the concepts of defense and psychic apparatus, the Freudian effort to spatialize this apparatus and the quality of the fabricated image of the fetish. This step allowed a first relationship between imagetic and historical aspects. Henceforth, we follow the creation of Verleugnung in Freud‘s work, from the defense theory and through his analysis of the two Moses, the text and the statue, as well as of Da Vinci and his paintings. We added the photography to the series that contains the biblical texts and the works of art, which made it possible to approximate the concepts of the unconscious, in Freud, and the optical unconscious, in Benjamin, and we verified that the functioning of the apparatus determines forms of historical production. Still, the resumption of these analyzes by Freud allowed a clinical differentiation between repression and denial according to their modes of return. While one requires interpretation, the other, creation. We also found an ethical dimension of this differentiation which refers to the realization of the meaning denied as a letter. Finally, we highlight how the freezing operated in photography, as a resolved contradiction and as a metonym of something seen and eternalized, indicts denial. We emphasize the importance of this indication in discussions in history for disarticulating the field of the seen to the totality of experience.